Maize-based systems as affected by forage grass and nitrogen fertilization: elucidating 15N recovery, greenhouse gas emissions, N-cycle functional genes in soil and crop yields - Grassmann, Camila da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Due to the interest in N use efficiency (NUE) and sustainable agricultural systems, the adoption of integrated systems, such as the intercropping of maize with forage grasses can be of great relevance, allowing the use of the land throughout the year, besides avoiding losses of N through nitrate (NO3 - ) leaching, nitrous oxide (N2O) emissions, ammonia volatilization (NH3), and immobilization. Tropical forage grasses of the genus Megathyrsus and Urochloa can suppress soil–nitrification by releasing inhibitory substances, reducing N losses and increasing fertilizer N recovery of the cash crop in rotation. In this way, understanding the N transformations in the soil by microorganisms and the fertilizer recovery in the system are very important. Firstly, the first two chapters are about a 3-year (2014-2017) field experiment conducted in southeastern Brazil, were forage grasses Guinea grass (Megathyrsus maximus cv. Tanzânia), palisade grass (Urochloa brizantha cv. Marandu), and ruzigrass (Urochloa ruziziensis cv. Comum) were cultivated in rotation with maize for grain in summer, to analyze the influence of forage grass and N fertilization in each study. In first chapter, maize was fertilized with 140 kg ha-1 N as (15NH4)2SO4 or not fertilized, and recovery of residual 15N was quantified in the second season. In second chapter, the change was that the N source used was ammonium sulphate not labeled, and were analyzed nitrous oxide (N2O), methane (CH4), and NH3 emissions from the system. In the third and fourth chapter, maize was intercropped with the same grasses previously mentioned. The N rates were 90, 180 and 270 kg ha-1 N and treatments without N fertilization. The objective was also to ascertain the effect of grasses and N fertilization from the analyzes carried out. The third chapter characterized the changes in N-cycle genes in the soil and measured the N2O emissions. The fourth chapter assessed maize grain yield and forage production, bromatological quality, and estimated meat production. In the first season after 15N application, 21%, 65%, and 33% of the N in maize grain, stover, and shoots, respectively, was derived from fertilizer. In the next season, of the total N found in maize grain, stover, and shoots, 2.2%, 1.9%, and 2.0%, respectively, was derived from the residual fertilizer applied in the previous year. There were no differences between forage grass species in the amount of 15N recovered by maize, soil, and total N. In the first season of maize in rotation with forage grasses, Guinea grass, palisade grass, ruzigrass did not affect N2O and NH3 emission due to their apparent inability to suppress soil nitrification. However, N fertilization slightly increases cumulative N2O emission. In maize intercropping with grasses, N fertilization increases the abundance of AOB (amoA of bacteria) more than AOA (amoA of archaea). N2O emission was influenced by AOB, water-filled pore space (WFPS) and N fertilization. Nitrogen fertilization positively affects forage growth and nutritional quality, resulting in a higher maize grain yield, higher forage production and quality, and eventually higher estimated meat production. Moreover, Guinea grass resulted in the highest estimated meat production when fertilized with 270 kg ha-1 N. However, no evidence of biological inhibition by the grasses were confirmed.

Devido ao interesse na eficiência no uso do N (NUE) e em sistemas agrícolas sustentáveis, a adoção de sistemas integrados, como o consórcio de milho com gramíneas forrageiras, pode ser de grande relevância, permitindo o uso da terra ao longo do ano, além de evitar perdas de N por lixiviação de nitrato (NO3-), emissões de óxido nitroso (N2O), volatilização de amônia (NH3) e imobilização. Gramíneas forrageiras tropicais do gênero Megathyrsus e Urochloa podem suprimir a nitrificação do solo ao liberar substâncias inibidoras, reduzindo as perdas de N e aumentando a recuperação de N fertilizante da cultura comercial em sucessão. Desta forma, o entendimento das transformações do N no solo por microrganismos e a recuperação do fertilizante no sistema são muito importantes. Em primeiro lugar, os dois primeiros capítulos são a respeito de um experimento de campo de 3 anos (2014-2017) conduzido no sudeste do Brasil, onde gramíneas forrageiras capim colonião (Megathyrsus maximus cv. Tanzânia), capim braquiária (Urochloa brizantha cv. Marandu) e capim braquiária (Urochloa ruziziensis cv. Comum) foram cultivadas em rotação com milho para grão no verão, para analisar a influência da gramínea forrageira e da fertilização com N em cada estudo. No primeiro capítulo, o milho foi fertilizado com 140 kg ha-1 de N na forma de (15NH4)2SO4 ou não fertilizado, e a recuperação do 15N residual foi quantificada na segunda safra. No segundo capítulo, a mudança foi que a fonte de N utilizada foi o sulfato de amônio não rotulado, e foram analisadas as emissões de óxido nitroso (N2O), metano (CH4) e NH3 do sistema. No terceiro e quarto capítulos, o milho foi consorciado com as mesmas gramíneas mencionadas anteriormente. As doses de N foram 90, 180 e 270 kg ha-1 e os tratamentos sem adubação nitrogenada. O objetivo também foi verificar o efeito das gramíneas e da fertilização com N a partir das análises realizadas. O terceiro capítulo caracterizou as mudanças nos genes do ciclo N no solo e mediu as emissões de N2O. O quarto capítulo avaliou o rendimento de grãos de milho e a produção de forragem, a qualidade bromatológica e a estimativa da produção de carne. Na primeira safra após a aplicação de 15N, 21%, 65% e 33% do N no grão de milho, palha e brotos, respectivamente, foi derivado de fertilizante. Na safra seguinte, do total de N encontrado nos grãos, caules e ramos de milho, 2,2%, 1,9% e 2,0%, respectivamente, foram derivados do fertilizante residual aplicado no ano anterior. Não houve diferenças entre as espécies de gramíneas forrageiras na quantidade de 15N recuperado pelo milho, solo e N. total. Na primeira temporada de milho em rotação com gramíneas forrageiras, capim-Guiné, capim-paliçada, ruzigrass não afetou a emissão de N2O e NH3 devido à sua aparente incapacidade de suprimir a nitrificação do solo. No entanto, a fertilização com N aumenta ligeiramente a emissão cumulativa de N2O. No consórcio de milho com gramíneas, a fertilização com N aumenta a abundância de AOB (amoA de bactérias) mais do que AOA (amoA de arquéias). A emissão de N2O foi influenciada por AOB, espaço poroso cheio de água (WFPS) e fertilização de N. A fertilização nitrogenada afeta positivamente o crescimento das forragens e a qualidade nutricional, resultando em maior rendimento de grãos de milho, maior produção e qualidade das forragens, e eventualmente maior produção de carne estimada. Além disso, o capim colonião resultou na maior produção de carne estimada quando fertilizado com 270 kg ha-1 N. No entanto, não foram confirmadas provas de inibição biológica por parte das gramíneas.
Sistemas baseados em milho afetados por gramíneas forrageiras e fertilização nitrogenada: elucidando a recuperação de 15N, emissões de gases de efeito estufa, genes funcionais do ciclo do nitrogênio no solo e produtividade das culturas
Keywords: Soil fertility; Nitrogen cycle; Forage plants Soils; Greenhouse gases; Fertilidade do solo; Ciclo do nitrogênio; Gramíneas forrageiras